SISTEMA DE SEGURANÇA PÚBLICA NO BRASIL: uma avaliação política do Plano Nacional de Segurança Pública e Defesa Social (2021-2030) no contexto da pós- redemocratização do país - MESQUITA, Silvio Carlos Leite (2024)
This thesis addresses public security policy as the object of its investigation, developing a political assessment of the National Plan for Public Security and Social Defense (2021-2030), established by Decree nº 10.822/2021, the main legal instrument for implementing the National Public Security and Social Defense Policy. Social Defense (Law 13.675/2018). In the process of analyzing the object, it was assumed that the creation of the National Public Security and Social Defense Policy (PNSPDS) together with the establishment of the Unified Public Security System (SUSP) by Law 13.675/2018 constitutes a divider of waters in the trajectory of public security in Brazil. The PNSP defines goals, strategies, objectives and a governance system that guide public security policies over the course of a decade, organized into biennial implementation cycles. The analysis will extend to assess whether the PNSP, as a national policy, is aligned with the design of the National Public Security and Social Defense Policy (PNSPDS) and whether it is capable of providing better public security conditions, access to rights and inducing the improvement of management and governance of public security in Brazil. In this way, the research aims to understand not only the PNSP formulation processes, but also its adequacy to social demands and the guidelines and objectives established by the PNSPDS, aiming to contribute to the improvement of public security policies in the country. The comprehensive method was adopted, considered appropriate for analyzing the process of formulating Public Policies, as well as the bibliographic and documentary methodological procedure. The political-normative panorama that conditioned the institution of the policy is presented, as well as the subjects who influenced the adoption of the National Public Security Policy. The fundamentals of the Policy were also addressed, as well as the contradictions between the interests of the Policy and the fight against violence. Finally, the process of formulating the National Public Security and Social Defense Plan 2021-2030, analyzing its historical context, the challenges faced and future expectations. As a result, the need for integrated, systemic and collaborative governance for effective public security in Brazil stands out, emphasizing the importance of a multidisciplinary approach that considers the historical and social causes of violence. From then on, there is an urgency for public policies that integrate the government, civil society and local communities. Furthermore, the research highlights that violence is a complex and multi-causal phenomenon, requiring strategic strategies focused primarily on preventing violence and promoting social equality, improving society's quality of life.